Alternative sites for laparoscopic cholecystectomy, in thin and obese patients from the point of view of changes in the abdominal dimensions - Ahmed, Hiwa Omer (Advances in Social Sciences Research Journal, 2015)
Background: Laparoscopic cholecystectomy is the standard operation for treatment of gallstone disease, which is difficult in obese patients, but narrow abdomen and thin patients are also a challenge, resulting in complications which mainly affect patients at the extreme ends of the weight spectrum. This represents a major source of morbidity and mortality from laparoscopic procedures; the majority (80%) of these complications is due to placement of the primary trocar, Searching for techniques to prevent involuntary injuries must be put as the priority, to ensure the optimal retraction, allows enough space available for manipulation of the active jaws of the laparoscopic graspers or scissors. Aim: To define alternative sites for laparoscopic cholecystectomy, in thin and obese patients from the point of view of alteration in the abdominal dimensions, which may reduces laparoscopic, related injury. Methods: In Al Sulaimaniyah Teaching Hospital and Hatwan Private Hospitral , from (July 15th 2004-July14th 2009) 1076 patients underwent laparoscopic cholecystectomy by same team and 35% of them by the same surgeon. Standard 4 ports were used, with first entry port in the periumblical region. Sixty patients were selected, because of their extreme weight and the patients were classified accordingly in to two groups: Group A:had downward displacement of umbilicus (43-60 cm width & 30-45cm height of the abdomen). Group B; had narrow abdominal dimensions (28-38 cm width & 14-27cm height of the abdomen). Results: Different alternative sites for trocar insertion were selected in order to overcome abdominal thickness and discrepancy between length of the hand instruments and distance of the port to the gall bladder Conclusions: We recommend using this principle in the patients with extreme weight and narrow abdomen when XU is less than 15 cm or (more than 25cm), to decrease challenges of sequel of laparoscopic cholecystectomy in these groups of patients.